Politeness Strategies Employed in Communication with Santri and Ustadz in an Islamic Boarding School in Indonesia - Zakaria, Bahrudin Nur Aziz; Fakih, Muhammad Nur; Saifuddin, Saifuddin; Imani, Aliakbar; Said, Hamdan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study on politeness and morals is a learning strategy used in the interaction between santri and kyai/ustdaz in Pesantren Salaf Al-Qur'an Sholahul Huda Al-Mujahidin. This study examined the politeness strategies of both santri and kyai/ustadz in their daily interactions and the factors underlying their use of such systems. Further, a case study qualitative approach by doing observation and interview was employed as the study method. To figure out the phenomenon, Brown and Levinson's theory of politeness strategies was applied in analyzing the data: Bald on Record, positive politeness, negative politeness, and off Record. From the analysis, it was figured out that all types of politeness strategies were realized in kyai/ustadz utterances. In contrast, only three politeness strategies were performed by santri. It was identified that some social factors of power and social distance triggered the santri and kyai/ustadz to execute such plans. However, another influential factor that was found to encourage the participants to employ those strategies was Pesantren Sholahul Huda Al-Mujahidin's culture of akhlak encompasses several values based upon Islamic values declared in Al Quran and Al Hadith. Maintaining and nurturing this Akhlak and morality is believed to be the basis of the realization of peace.